Behavioral Factors of Internal Auditors and Enterprise Risk Management Effectiveness Assessment of Malaysian Statutory Bodies - Mohd Saleh, Norman; Wan Chik, Mohd Nurfirdaus (UUM Press, 2022)
This study used the theory of planned behavior to examine the relationship between internal auditors’ behavioral factors and intention to evaluate enterprise risk management (ERM) effectiveness of Malaysian statutory bodies. Unlike prior literature, this study also included a test on individual attitude towards risk in addition to attitude towards behavior, subjective norms, and perceived behavioral control. Analysis on 108 received responses showed that subjective norms and perceived behavioral control had positive relationships with the intention to assess ERM effectiveness. Nevertheless, the influence of attitude was not substantiated. The results imply that attitude is not an important factor when individuals do not have total process ownership. Managers of statutory bodies and heads of internal audit departments need to shape internal auditor behavior by instituting social and administrative norms and instilling a positive perception about the ability to perform tasks within the organization. This study also shows that individuals have no total ownership in a process, thus focusing efforts on shaping individual attitude is not practical. This issue is critical because successful ERM implementation depends on internal auditors’ intention to evaluate its effectiveness. An effective ERM can reduce the risks of waste, inefficiencies, corruption, malpractices, and public–private partnerships associated with the public sector.